Organic and Inorganic Fertilizers on the Growth of Chili Plants: a Comparative Analysis - Maheswara Rabbani (Cakrawala Repositori IMWI, 2023)
The purpose of this study was to analyze the comparison of organic fertilizers and inorganic fertilizers to the growth of chili plants. In general, fertilizers are divided into two groups: organic and inorganic. The types of fertilizers produced by fertilizer producers have been increasingly diverse and spread in the market. However, what is comparable to buying fertilizer is the elements in the fertilizer itself. The method used in this study was an experimental method by testing the growth of five pots of chili plants that were given compost (organic) and five pots that were given NPK (inorganic) fertilizer. After 40 days of observation, plants that were given organic grew taller than plants that were given inorganic fertilizers. Chili plants with organic fertilizers experienced an increase in plant height by 42.94 cm from an initial height of 45.4 cm to 88.34 cm. Meanwhile, chili plants with inorganic fertilizer experienced an increase in plant height by 35.04 cm from the initial height of 45.4 cm to 80.04 cm. This happens because of the difference in the content of the two fertilizers.